2004
DOI: 10.1007/s00477-004-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic groundwater models in practice

Abstract: Question 1: Why have there not been many real-world applications of stochastic theories and approaches, despite the significant progress in developing such rigorous theories and approaches for studying fluid flow and solute transport in heterogeneous media?Among the reasons for this state of affairs I count the following:There is a perception among groundwater hydrologists that real-world applications of stochastic concepts and models require numerous reliable measurements of spatially-variable hydrogeologic q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Discussions regarding to the limitations of MCS have been made in many previous studies (e.g. Neuman, 1999, Kunstmann andKinzelbach, 2000;Zhang, 2002, Feyen et al, 2003aBallio and Guadagnini, 2004;Dagan, 2004;Neuman, 2004;Li et al, 2003, 2004a, b, Ni and Li, 2005.…”
Section: Introductionmentioning
confidence: 97%
“…Discussions regarding to the limitations of MCS have been made in many previous studies (e.g. Neuman, 1999, Kunstmann andKinzelbach, 2000;Zhang, 2002, Feyen et al, 2003aBallio and Guadagnini, 2004;Dagan, 2004;Neuman, 2004;Li et al, 2003, 2004a, b, Ni and Li, 2005.…”
Section: Introductionmentioning
confidence: 97%
“…Direct calculation shows the estimator (60) for the mean η̄ converges subject to the estimate (61) where σ is the standard deviation of η. As the mean η̄ is unknown, convergence may be conveniently judged by examining the fluctuation sizes between successive estimates; the fluctuation of ηN with lag k is given by (62) where σ 2 is the variance of η, and the log-fluctuation of the standard deviation is therefore (63) when N ≫ k.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…Certain pitfalls must be avoided when using MC methods: for example, the pseudorandom variates used for simulation can fail in important ways [53]. These methods are not easily conditionalized [61], and their slow convergence has led to interest in acceleration techniques [13,30]. Transformation of the underlying probability space using importance sampling was suggested in [49], using a spatially constant random conductivity field with one-dimensional flow, but to the best of our knowledge it has not been considered for nontrivial stochastic flow problems.…”
Section: Introductionmentioning
confidence: 99%
“…Proper depiction of the spatial variability of hydraulic attributes (e.g., hydraulic conductivity and porosity) on the basis of commonly available information at scales which are relevant for groundwater flow and transport modeling is a key issue in stochastic hydrogeology (e.g., Dagan 2004;Neuman 2004). Gégo et al (2001) showed that stochastic simulations with uniform conductivity assigned to different (randomly distributed) litho-facies do not necessarily provide a good representation of the uncertainty associated with the system.…”
Section: Introductionmentioning
confidence: 99%